The Cost of Excessive Smartphone Use: Guilt Cross the Work-Family Domains - Liu, Yujing; Du, Jing; Li, Yuan (Frontiers in Psychology, 2021)
Empirical evidence has accumulated showing that smartphone use at work has the double-edged sword impacts on work-related attitudes and behaviors, but little is known about how its effects transmit and spill over from the workplace to the family domain. Drawing upon compensatory ethics theory, we hypothesize positive associations of employees’ daily private smartphone use at work with their family role performance after work through feeling of guilt. Using an experience sampling methodology, we test our hypotheses in a sample of 101 employees who completed surveys across 10 consecutive workdays. Multilevel path analysis results showed that excessive smartphone use at work triggered experienced guilt, and had a positive indirect effect on family role performance via feeling of guilt. Furthermore, employees with high ability of emotion regulation can be better resolve own painful emotion by engaging in family role performance. Theoretical and practical implications, limitations, and propose future research directions are discussed.